The Effect Of Health Education About Balanced Nutrition On The Level Of Pregnant Women Knowledge Who Suffers Chronic Energy Lacks - Fitriani; Asnidar; Suhartini Suardi (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
Chronic Energy Deficiency is a condition of lack of energy and protein intake in Pregnant Women that continues and has an impact on the health and safety of infants. Based on the prevalence of KEK pregnant women in the Balangnipa Puskesmas UPTD, in 2018 there were 170 (19.32%) Pregnant women suffering from SEZ from 880 visits by pregnant women. The occurrence of nutritional problems in pregnant women is generally caused by unbalanced eating patterns while fulfilling nutrition during pregnancy must have the motivation that is supported by sources of information and knowledge through health education about balanced nutrition. This study was intended to determine the effect of health education on balanced nutrition on the level of knowledge of pregnant women who suffer from KEK. The study was conducted with a pre-experimental method with the design of One Group PreTest-PostTest, the population consisted of 72 people, and techniques The sampling used is Purposive Sampling with a sample of 42 KEK Pregnant Women, with research instruments using a questionnaire. Data analysis is a Categorical Comparative Test using a paired T-Test. Based on data analysis, it is known that the level of knowledge of SEZ pregnant women before being given health education is 5 (11.9%) respondents with a good knowledge category, whereas after being given health education is 28 (66.7%) respondents with good knowledge category. This change was seen from the mean value of 15.33 (SD 5,318) to 25.31 (SD 3,639) with (p-value: 0,000 or Î± <0.001). This research shows that there is an effect of health education on balanced nutrition in pregnant women who suffer from KEK. Therefore, it is expected that the SEZ problem will get good treatment, and counseling on nutrition will be improved, with the development of more adequate references.